PENINGKATAN KUALITAS DAN KUANTITAS OLAHAN RUMPUT LAUT COTTONII PADA UKM KELOMPOK TANI MANGROVE WONOREJO RUNGKUT - Lila Yuwana; Susilo Indrawati; Iim Fatimah; Sudarsono Sudarsono; Melania Suweni Muntini; Suyatno Suyatno (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2022)
In this community services, cottoni seaweed processed products have been developed which are widely obtained in mangrove forest areas, mangroves, Rungkut Surabaya. Moreover, the production capacity has been increased so that production per day can increase significantly, i.e, to the double if using the equipment provided in this activity. Furthermore, the production process will also be accelerated so that not only the quantity of products per day is improved, but also the production time can be accelerated and the production process will be much more efficient. With the existence of this community services, it has also succeeded in increasing the diversification of processed products made from local raw materials efficiently and with a large production capacity. It has been produced that the production capacity is doubled per day if using the mixer equipment provided by the service team. Furthermore, by using a spinner that is also provided by the community services team, quality improvement is attained by slicing oil for processed fried foods.